2010
DOI: 10.1111/j.1463-1326.2010.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic uses for ezetimibe beyond lowering LDL‐c to decrease cardiovascular events

Abstract: Ezetimibe is a relatively new drug that inhibits the absorption of dietary cholesterol in the small intestine. It is a low density lipoprotein-cholesterol (LDL-C) lowering medication that acts directly on the intestine by inhibiting Niemann-Pick C1 Like1 (NPC1L1). Recently, results of the ARBITER 6-HALTS trial (Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol 6-HDL and LDL Treatment Strategies) and the ENHANCE trial (Ezetimibe and Simvastatin in Hypercholesterolemia Enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…This is consistent with the SREBP pathway. Recent evidence suggests that NPC1L1 may affect transcription factors responsible for regulating insulin sensitivity and lipid metabolism (84). Several studies have shown that inhibition of NPC1L1 in rats significantly reduces cholesterol uptake, lowers weight gain, and decreases insulin resistance (85)(86)(87).…”
Section: Inflammation Decreases Benefits Of Diet Interventionsmentioning
confidence: 99%
“…This is consistent with the SREBP pathway. Recent evidence suggests that NPC1L1 may affect transcription factors responsible for regulating insulin sensitivity and lipid metabolism (84). Several studies have shown that inhibition of NPC1L1 in rats significantly reduces cholesterol uptake, lowers weight gain, and decreases insulin resistance (85)(86)(87).…”
Section: Inflammation Decreases Benefits Of Diet Interventionsmentioning
confidence: 99%
“…However, a recent survey estimated that 1/200 of the general population is heterozygous for familial hypercholesterolemia due to LDL receptor mutation, and a large proportion of these individuals failed to achieve recommended cholesterol levels upon statin therapy [17]. The advent of ezetimibe to block intestinal cholesterol absorption has provided an alternative strategy to reduce plasma cholesterol levels and decrease atherosclerosis risk [18]. The current study showing the effectiveness of Pla2g1b inactivation to reduce plasma cholesterol levels and suppress atherosclerosis in animals with LDL receptor deficiency suggests another novel strategy through Pla2g1b inhibition to enhance hepatic fatty acid oxidation for treatment of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low-carbohydrate diets increase the risk of both calcium and uric acid stones. 43,44 Therefore, it is possible to conclude that metabolic syndrome and treatment of metabolic syndrome are associated with an increase in risk of renal stone disease.…”
Section: Obesity and Renal Stone Disease And Cholesterol Gallstonesmentioning
confidence: 99%